Cancer Immune Checkpoint Inhibitor Therapy and the Gut Microbiota. (April 2019) - Frankel, Arthur E.; Deshmukh, Sachin; Reddy, Amit; Lightcap, John; Hayes, Maureen; McClellan, Steven; Singh, Seema; Rabideau, Brooks; Glover, T. Grant; Roberts, Bruce; Koh, Andrew Y.
The past decade has seen tremendous advances in both our understanding of cancer immunosuppressive microenvironments and colonic bacteria facilitated by immune checkpoint inhibitor antibodies and next generation sequencing, respectively. Because an important role of the host immune system is to communicate with and regulate the gut microbial community, it should not come as a surprise that the behavior of one is coupled to the other. In this review, we will attempt to dissect some of the studies demonstrating cancer immunotherapy modulation by specific gut microbes and discuss possible molecular mechanisms for this effect.